Provenance performance of Macaranga tanarius (L.) Mull. Arg. in Peninsular Malaysia - Koter, Rosdi (2019)
Recognizing the importance of growth and yield studies of plantation-grown pioneer fast-growing species for future forest management decisions, coupled with a general need of knowledge on the growth and potential yield of the species planted under plantation condition. Macaranga tanarius is considered among the Macaranga species that can be an excellent alternative source due to the availability and high yield of seeds throughout the year. This study is expected to provide some necessary information needed to verify M. tanarius as a potential species for forest plantation. The data generated on growth and potential of the species can be used in planning for the establishment and management of M. tanarius plantation in the future. This species was found to have a broad distribution, living in groups, producing male and female flowers on separate trees, and flowering throughout the year. M. tanarius was found mass flowering twice a year. In the wild, the seeds took two months to germinate. M. tanarius seeds were obtained from four provenances in Peninsular Malaysia, namely Northern, Southern, Eastern, and Central provenances for the collection of wildings as a source of planting material used in the experimental plots. For quality and germination ability in the laboratory, the seeds were obtained from six female trees in Kepong, Selangor. M. tanarius seeds were found to be able to germinate better upon soaking in water at room temperature rather than in hot water with a germination rate of 68% and 0%, respectively. The seeds started to germinate after two weeks and lasted for another two weeks. Three plant growth regulators (PGR), namely GA3, BAP and kinetin at three concentrations were also applied to the seeds as a pretreatment to test germination. The application of GA3 at 10 mgl-1 only managed to result in 40% germination. The seedlings from the four provenances were then raised in the nursery for 16 months. Total biomass was calculated from each plant part namely, roots, stems, branches and leaves. The proportion of biomass calculated was stem > roots > leaves > branches. Both fresh and dry-biomass showed significant differences (p<0.05) between provenances in all parts. The Northern provenance showed the highest mean dry-biomass value, followed by the Eastern, Southern, and Central. For provenance trial, wildings from each provenance were collected and planted at four established plantation plots in SPF Jeli (Eastern region), SPF Mata Ayer (Northern region), SPF Selandar (Southern region), and Field 52 Bukit Hari, FRIM HQ (Central region). The trial was laid out in a randomized complete block design with three replications, and 16 or 25 seedlings per replicate depending on the size of plantable areas. Growth performance of M. tanarius was evaluated based on height, root collar diameter, and survival rate. Assessments were made for 18 months at 3-month intervals. Overall, all provenances showed the highest total height in SPF Jeli > SPF Selandar > Field 52 > SPF Mata Ayer. The Central provenance showed the highest total height over other provenances. Root collar diameter and survival rate for most provenances ahow a similar trend for Jeli and Selandar. All provenances were well adapted and performed well in their growth, and significantly differerent between genotype and the environment. Variation, however, exists in height, root collar diameter, survival, and biomass. Based on the results of this study, M. tanarius is a promising pioneer species for forest plantation, but further study needs to be carried out, including exploring genetic make-up of the various provenances.